From Group–level to the Individual: A Mixed Methods Study on Language Anxiety and its Connections to L2 Speech Fluency among Finnish Upper Secondary School Students - Korkka, Otava (My University, 2024)
This thesis focuses on the connections between L2 fluency and language anxiety among a group of 27 Finnish upper secondary school students. The aim of the study was to investigate the connection between language anxiety and L2 speech fluency by examining both group tendencies and individual features. The research questions focused on extent to which Finnish upper secondary school students report experiencing language anxiety, to what extent their language anxiety correlates with their L2 fluency measures, and what kinds of individual features regarding their language anxiety, L1 and L2 fluency measures, and L2 proficiency can be found among the participants. The data consists of questionnaire answer, monologue recordings, post–session survey answers, and LexTale scores. The questionnaire measured the participants’ language anxiety. The monologue recordings were made in both L1 Finnish and L2 English, and the post–session survey measured the task–specific anxiety felt during the monologue task. LexTale is an English proficiency test that was used to gauge the level of participants’ language skill. The study uses a mixed methods approach, employing both quantitative and qualitative measures to examine the data. The findings of the study showed that there is some variation in the levels of reported language anxiety of Finnish upper secondary school students. While the average levels of anxiety were not high, there were some students who had very low or very high anxiety. Additionally, there was variation within the answers to single questions as well: usually both ends of the answer scale were used. As for the correlations between L2 speech fluency and language anxiety, language anxiety was found to correlate positively with overall silent pauses, as well as clause boundary and mid–clause silent pauses, suggesting that more anxious students produce more disfluencies. Speech rate and repair ratio correlated negatively with language anxiety, indicating that less anxious students speak faster. Some of the participants were found to have distinct individual features, such as inventing humorous details in their monologue. The participants also had similarities in terms of their reported reasons for anxiety during the monologue tasks. Overall, the findings suggest that the connection between language anxiety and fluency has grounds for further study, which could potentially help anxious language learners cope with their fears better.
Keywords: speech fluency, language anxiety, mixed methods